2006
DOI: 10.1037/0033-2909.132.5.667
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analytic review of obesity prevention programs for children and adolescents: The skinny on interventions that work.

Abstract: This meta-analytic review summarizes obesity prevention programs and their effects and investigates participant, intervention, delivery, and design features associated with larger effects. A literature search identified 64 prevention programs seeking to produce weight gain prevention effects, of which 21% produced significant prevention effects that were typically pre to post effects. Larger effects emerged for programs targeting children and adolescents (versus preadolescents) and females, programs that were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

23
571
4
19

Year Published

2007
2007
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 573 publications
(619 citation statements)
references
References 112 publications
23
571
4
19
Order By: Relevance
“…This effect size corresponds to 21.3% non-overlap between the intervention and the control conditions according to Cohen's interpretation. 60 Results of the analyses of studies using TV reduction, nutrition alone and physical activity alone should be interpreted cautiously, as only one study was available in each category. Nevertheless, these results indicate that the major contributing factor to the success of combination nutrition and physical activity interventions may be the nutrition component.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This effect size corresponds to 21.3% non-overlap between the intervention and the control conditions according to Cohen's interpretation. 60 Results of the analyses of studies using TV reduction, nutrition alone and physical activity alone should be interpreted cautiously, as only one study was available in each category. Nevertheless, these results indicate that the major contributing factor to the success of combination nutrition and physical activity interventions may be the nutrition component.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analytic review of 64 obesity prevention programs (46 trials) for children and adolescents showed that 79% of programs did not produce statistically reliable weight-gain-prevention effects. 60 Another systematic review examining interventions for childhood obesity prevention also reported that the majority of studies reviewed did not have a significant impact. 22 These results suggest that the demonstration of weight loss among overweight children may be more easily attainable than the demonstration of the prevention of weight gain.…”
Section: Discussionmentioning
confidence: 99%
“…8 Obesity prevention interventions targeting these lifestyle behaviors (that is, increasing physical activity and improving diet) have had limited success, as the establishment of healthy behaviors is difficult to sustain in the long term. [9][10][11] In a recent Cochrane review of 22 randomized controlled trials, Summerbell et al 9 found that childhood obesity prevention interventions resulted in no reduction of overweight (that is, body mass index (BMI)) and only modest improvements in changing diet or exercise behaviors in the short term. 9 Nonetheless, modification of these lifestyle behaviors continues to be recommended for obesity prevention in children.…”
Section: Introductionmentioning
confidence: 99%
“…Although CBT prevention programs have produced promising findings, the duration of these interventions makes them challenging to implement in schools. Thus, the first aim of the present study was to develop and evaluate a briefer CBT intervention in the hope that its shorter duration would increase its appeal to adolescents and ease of implementation, facilitating subsequent dissemination.We developed a targeted intervention because prevention trials for depression, eating disorders, obesity, aggression, and substance abuse suggest that intervention effects are stronger for people with elevated symptoms versus the general population (Horowitz, & Garber, 2006;Stice & Shaw, 2004;Stice, Shaw, & Marti, 2006). Those who are struggling with elevated symptoms may be more motivated to engage in prevention programs and may more easily acquire the intervention skills by applying them to their current experiences.…”
mentioning
confidence: 99%
“…We developed a targeted intervention because prevention trials for depression, eating disorders, obesity, aggression, and substance abuse suggest that intervention effects are stronger for people with elevated symptoms versus the general population (Horowitz, & Garber, 2006;Stice & Shaw, 2004;Stice, Shaw, & Marti, 2006). Those who are struggling with elevated symptoms may be more motivated to engage in prevention programs and may more easily acquire the intervention skills by applying them to their current experiences.…”
mentioning
confidence: 99%